THE INFLUENCE OF FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE, AND LOCUS OF CONTROL ON FINANCIAL MANAGEMENT BEHAVIOR IN EMPLOYEE CLASS S1 STUDENTS IN MANAGEMENT STUDY PROGRAM FACULTY OF ECONOMICS AND BUSINESS NATIONAL UNIVERSITY - Azizah Azizah; Kumba Digdowiseiso (SEAN Institute, 2023)
The study aims to determine the effect of financial attitude, financial knowledge, and locus of control on financial management behavior in undergraduate students in the employee class of the Management Study Program, Faculty of Economics and Business, National University. The research uses primary data obtained from respondents through distributing questionnaires. The sample in this study was 100 respondents from 220 undergraduate students in the Employee Class of the Faculty of Economics and Business, National University. Descriptive analysis and multiple linear regression analysis are data analysis techniques used in this study using STATA version 17.0. Based on the research that has been done, it shows that the Financial Attitude variable has a positive but not significant effect on Financial Management Behavior, on the other hand Financial Knowledge and Locus Of Control have a positive and significant effect on Financial Management Behavior in S1 students in the Employee Class Management Study Program, Faculty of Economics and Business, National University.